Gegar Budaya dalam Webtoon Next Door Country - Chyntia Devi; Sumekar Tanjung (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2020)
This study aimed to explain the cultural shock reaction experienced by foreigner in the context of Indonesian culture, especially in Aditiya Wahyu Budiawan's Webtoon Next Door Country. This research employed Roland Barthes' semiotic analysis to analyze three episodes from mentioned Webtoon series. The findings showed that in Next Door Country Webtoon, foreigners often to use facial expression when dealing with customs and cultural traditions in Indonesia. In this Webtoon, facial expression is used as a form of emotional expression to show the emotions they feel as a result of culture shock phenomenon experienced in the process when experiencing and understanding a new culture. During the process of cultural shock, foreigners as in Webtoon will go through four phases; those are optimistic phase, crisis phase, recovery phase, and adjustment phase. Another finding from this research is that the diverse cultural tradition in Indonesia is the main trigger for these foreigners to experience cultural shock.